Metagenomic analysis identifying a polymicrobial pulmonary infection in a non-HIV immunocompromised patient: a case report - Jing Duan; Jie Ding; Yupeng Wei; Yingxin Zhang; Zhiqing You; Ding Li; Chao Chen (BMC Pulmonary Medicine)
Abstract Background Polymicrobial pulmonary infections, common in immunocompromised patients, often manifest more severe symptoms than monomicrobial infections. Clinical diagnosis delays may lead to mortality, emphasizing the importance of fast and accurate diagnosis for these patients. Metagenomic next-generation sequencing (mNGS), as an unbiased method capable of detecting all microbes, is a valuable tool to identify pathogens, particularly in cases where infections are difficult to diagnosis using conventional methods. Case presentation A 50-year-old male patient was admitted due to cough, expectoration and dyspnea. CT scan revealed diffuse inflammatory and cavernous lung lesion, and blood examination suggested a polymicrobial infection. However, no etiology was found by routine examination. mNGS of bronchoalveolar lavage fluid(BALF)simultaneously detected the presence of Pneumocystis jirovecii (P.jirovecii), Aspergillus fumigates (A.fumigates), Nocardia farcinica (N.farcinica), Salmonella enterica subsp. enterica (S.enterica subsp. enterica), and cytomegalovirus (CMV). The patient was successfully treated with compound sulfamethoxazole (SMZ-TMP), cefoperazone/sulbactam (SCF), moxifloxacin (MXF), voriconazole (VCZ), and ganciclovir. The patient recovered after two weeks of anti-infection therapy and maintained good health at a six-month follow-up. Conclusion For immunocompromised patients with multiple infections and atypical symptoms, mNGS emerged as a reliable approach to pathogen detection and guiding antibiotic therapy.